KANDUNGAN MANGAN DALAM AIR SUNGAI RIAM KANAN DAN HATI IKAN NILA (Oreochromis niloticus L) DI KECAMATAN KARANG INTAN KABUPATEN BANJAR - Normaningsih Y (Bioscientiae, 2009)
A research in Manganese ion concentration in the water of Riam Kanan river and Nila’s liver (Oreochromis Niloticus L) has been conducted at Karang Intan district, Banjar Regency in September until Desember 2008. This research aims to detect manganese concentration in river’s water and nila’s liver. Sampling has been done at 3 locations i.e Tambela, Mandikapau Timur, and Pingaran Hulu. Samples were taken periodically every 2 weeks in 3 times. Analysis of manganese concentration use Spektrofotometry and AAS methods based on SNI protocol (SNI. 19-1133-1989 and SNI. 01-2891-1992). Result shows that manganese concentration’s average in Riam Kanan river’s water are average 0,267; 0,3; and 0,5 mg/L, which exceed than river’s water first class quality standard based on Governor Regulation of Kalimantan Selatan No. 05 in 2007. Manganese concentration’s average in nila’s liver are 0,027; 0,031; and 0,035 mg/kg, still below average concentration according to WHO.